Characteristics and recurrence of primary eyelid basal cell carcinoma in central Spain - Galindo-Ferreiro, Alicia; Sanchez-Tocino, Hortensia; Diez-Montero, Cecilia; Belani-Raju, Minal; Garcia-Sanz, Raquel; Diego-Alonso, Miguel; Llorente-Gonzalez, Ines; Perez, Patricia Callejo; Khandekar, Rajiv; Schellini, Silvana [UNESP] (Wolters Kluwer, 2020)
Purpose: To define the incidence, characteristics, and management of eyelid basal cell carcinoma (BCC) in Central Spain. Methods: This retrospective study investigates the characteristics and the outcome of eyelid BCC from 2000 to 2016 in a central region of Spain. Data were collected on demographics, skin phenotype, location of the eyelid lesion, clinical and histological diagnosis, surgery, commitment of surgical margins, and recurrence rate. Results: Primary eyelid BCC occurred in a mean of 20.6 lesions a year or 9.4/100,000 inhabitants/year. The mean age of BCC carriers was 69.4 ± 16.2 years, with no gender difference (P = 0.479), predominantly affecting Fitzpatrick II-III skin (81.3%) (P < 0.001). The most common location was the inner canthus (154/45.7%) (P < 0.001) and type nodular (215 cases/63.8%) (P < 0.001). The surgical margins were affected in 69 (20.5%) individuals, and the recurrence rate was 5.6 (95% confidence interval, 3.2-8.3) significantly higher in affected margins (P < 0.001). The most common location for recurrence was the inner canthus (P = 0.003), and the most common histological type for recurrence was sclerosing (16.7%), then multinodular (12.5%), and infiltrating (10.4%) with no significant difference (P = 0.27). Conclusions: The frequency of occurrence of eyelid BCC is much less than the estimated crude incidence for skin tumors involving all areas of the body in the Spanish population. Eyelid BCC is more common in the seventh decade of life, with no predilection for gender. Nodular histological type is the most common. The recurrence rate is 5.6%, depending on site and affected margins, even though clear free margins also can present with recurrence.
Keywords: Basal cell carcinoma; Eyelid tumors; Periocular; Spain